The Formation of the Innovative Economy of Sweden: Peculiarities and Prospects - N. V. Zakharova; A. V. Labudin (Управленческое консультирование)
In the article the performance & the formation of the innovation economy of Sweden are considered. The main peculiarities of the Swedish economy and also some stages of it’s performance and development are highlighted. The main achievements of the innovation system of Sweden and also the reasons for the success of the innovative economy in Sweden are analyzed. The strong & weak points of the innovation system of this country are determined.